2003
DOI: 10.1088/0957-0233/14/8/322
|View full text |Cite
|
Sign up to set email alerts
|

In situmeasurement of hydrocarbon fuel concentration near a spark plug in an engine cylinder using the 3.392  m infrared laser absorption method: application to an actual engine

Abstract: An infrared absorption method with a 3.392 µm He–Ne laser was used to determine the hydrocarbon fuel concentration near the spark plug in a spark-ignition engine. Iso-octane was used for the fuel. The pressure and temperature dependence of the molar absorption coefficient was clarified. The molar absorption coefficients of a multi-component fuel such as gasoline were estimated by using the coefficient of each component and considering the mass balance. A sensor was developed and installed in a spark plug, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…In the measurement of the absorbance, common mode rejection is used to minimize uncertainty related to laser stability and noise. The cross sections, as observed in previous work on a number of hydrocarbons , can decrease as the shock pressures and temperature increase. In previous studies, it was observed that the cross sections of cyclohexane, naphthene, and aromatic hydrocarbons decreased with increasing temperature and pressure.…”
Section: Experimental Approachsupporting
confidence: 76%
“…In the measurement of the absorbance, common mode rejection is used to minimize uncertainty related to laser stability and noise. The cross sections, as observed in previous work on a number of hydrocarbons , can decrease as the shock pressures and temperature increase. In previous studies, it was observed that the cross sections of cyclohexane, naphthene, and aromatic hydrocarbons decreased with increasing temperature and pressure.…”
Section: Experimental Approachsupporting
confidence: 76%
“…Several researchers have developed single-ended probes for studying IC-engines via IR-LAS [248,249,42,250,241,242]. Hall and Koenig [248] were the first to implement IR fibers into a spark-plug probe (similar to that shown in Figure 19) for delivering and receiving IR light.…”
Section: Probe-based Single-ended Sensorsmentioning
confidence: 99%
“…A similar configuration and diagnostic technique was more recently used by Cundy et al [250]. Tomita et al [249] used a similar probe design, but used two sapphire rods cleaved at 45 • to direct light in and out of the engine and used a HeNe near 3.39 μm to monitor fuel absorption. More recently, Rieker et al [42] integrated a fiber-coupled WMS-2f /1f -based TD-LAS sensor into a spark plug and demonstrated crankangle resolved measurements of temperature and H 2 O concentration in motored and fired tests.…”
Section: Probe-based Single-ended Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two wavelengths were selected so as not to the IR absorbing sensor. interfere with absorption bands of carbon dioxide and water based on the HITRAN database [25]. The light of 1.30 mm wavelength is used to sense the existence of fuel droplets and contamination of the sapphire rod surfaces.…”
Section: Figmentioning
confidence: 99%